Implementación de la plataforma tecnológica de recomendación como caso de estudio de mejora en la empresa DEBUG S.A.C. - Larrea Cardozo, Arturo Ernesto (2020)
DEBUG S.A.C is a company dedicated to the production of highly specialized software and has no presence in the market for non-specialized products. TRecomiendo is based on the platform of a project developed for a particular customer with the potential to develop to more industries. This platform rewards the recommendation of users who have already used the products. This project will demonstrate its technical, commercial and financial viability, in addition to verifying that they can reduce and DEBUG their sales in the non-specialized products market.